If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(8u + -7) + 4u = 2(u + 6) Reorder the terms: -2(-7 + 8u) + 4u = 2(u + 6) (-7 * -2 + 8u * -2) + 4u = 2(u + 6) (14 + -16u) + 4u = 2(u + 6) Combine like terms: -16u + 4u = -12u 14 + -12u = 2(u + 6) Reorder the terms: 14 + -12u = 2(6 + u) 14 + -12u = (6 * 2 + u * 2) 14 + -12u = (12 + 2u) Solving 14 + -12u = 12 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 14 + -12u + -2u = 12 + 2u + -2u Combine like terms: -12u + -2u = -14u 14 + -14u = 12 + 2u + -2u Combine like terms: 2u + -2u = 0 14 + -14u = 12 + 0 14 + -14u = 12 Add '-14' to each side of the equation. 14 + -14 + -14u = 12 + -14 Combine like terms: 14 + -14 = 0 0 + -14u = 12 + -14 -14u = 12 + -14 Combine like terms: 12 + -14 = -2 -14u = -2 Divide each side by '-14'. u = 0.1428571429 Simplifying u = 0.1428571429
| 2/3(x-6)-1/3(x-3) | | -2(8u-7)+4v=2(v+6) | | 2w^3+6w^2-4w=0 | | 90d=2 | | -(3-3n)=4(7+2n)+4 | | 81+2d= | | -2n+8(n-7)=-86 | | 6a^3-12a^2+14a=0 | | -3(2-1)=12 | | -2n+8(n-7)=-3-5(v+8) | | 18=69-24 | | L=b+c-dsolvec | | 10w+10+3w=6(9+w)-14 | | 8+7n-6-4n=n-8 | | (2x^2-13x+6)/(6x^2-x-1) | | 8x-9=41 | | 3m(m+4)=18 | | 6x-3=7x-10 | | 1/3(3x-2)=6-x | | 2n+3+8=1 | | 31.83D=5103 | | 1=1+n-1 | | -3y+2x=6 | | 2a-7=-2a+5 | | 291-13-8= | | 0=-4b-6b | | 291-(-13-8)= | | 291-(-13+-8)= | | r/4-7/4+3r/4=1/4 | | -7(3+v)=-77 | | s/5=-16 | | 28x^2-27x-10=0 |